Uporabnost programskega okolja Ro za urejanje lastninskih razmerij pri gradnji cest - Kovačič, Boštjan (Geodetski vestnik, 1997)
The arranging of ownership status for the construction of roads is a time-consuming task that causes much distress to the affected owners. The modern computer equipment and software based on GIS technologies can efficiently support the real estate buy-off process. The use of these technologies also allows us to update and supervise the parcel buy-off situation increasing the speed and quality of work.
Keywords: geodezija; GIS; gradnja cest; odkup; zemljišča; zemljiška posest